Burundi : Seventh Review Under the Three-Year Arrangement Under the Extended Credit Facility and Request for a New Three-Year Arrangement Under the Extended Credit Facility: Staff Report; Staff Supplement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Burundi. (IMF Staff Country Reports; Country Report ;, 2012)
Burundi's economy has continued to grow at a slower pace than envisaged owing to the impact of food and fuel shocks on aggregate demand. The macroeconomic outlook remains broadly positive but subject to risks that emanate from the security situation and the external environment. The foremost risks are a decline in donor support, warranting an abrupt fiscal adjustment, and a worsening in the security situation. These risks are mitigated in part by reforms that have improved revenue mobilization and efforts in nation building.